Solid Lipid Nanoparticles as Efficient Drug and Gene Delivery Systems: Recent Breakthroughs - Jafar Ezzati Nazhad Dolatabadi; Hadi Valizadeh; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2015)
In recent years, nanomaterials have been widely applied as advanced drug and gene delivery nanosystems. Among them, solid lipid nanoparticles (SLNs) have attracted great attention as colloidal drug delivery systems for incorporating hydrophilic or lipophilic drugs and various macromolecules as well as proteins and nucleic acids. Therefore, SLNs offer great promise for controlled and site specific drug and gene delivery. This article includes general information about SLN structures and properties, production procedures, characterization. In addition, recent progress on development of drug and gene delivery systems using SLNs was reviewed.